Density of Araceae in the River Basin Area of Lawua Village, South Kulawi District, Sigi Regency - Nurfitriani Nurfitriani; Samsurizal M Suleman; Moh Sabran; Isnainar Isnainar; Amalia Buntu; Musdalifah Nurdin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Araceae are herbaceous plants belonging to the monocotyledonous group of Angiosperms. They exhibit distinct morphological characteristics in their roots, stems, and leaves, and are generally herbaceous, with plant heights ranging from 90 to 180 cm. These plants hold significant economic and ecological value, as they are utilized as ornamental plants, food sources, and medicinal resources. This study aimed to identify and analyze the density of Araceae in the river basin area of Lawua Village, South Kulawi District, Sigi Regency. The research employed a descriptive qualitative and quantitative approach, with sampling conducted using the belt transect method across three different observation stations. Observations involved counting and recording the number of individuals of each Araceae species within the transect paths. Additionally, each species was documented, and samples were collected for identification based on their morphological characteristics, followed by density analysis. Overall, the study identified 16 Araceae species across 11 genera. These genera include: Alocasia (1 species), Colocasia (3 species), Dieffenbachia (1 species), Epipremnum (1 species), Homalomena (1 species), Pistia (1 species), Rhaphidophora (1 species), Scindapsus (2 species), Schismatoglottis (3 species), Spathiphyllum (1 species), and Syngonium (1 species). The overall density ranged from low to moderate, between 7 and 1,737 individuals, with abiotic conditions including an average temperature of 28 °C, humidity of 62.33%, light intensity of 2,998 Cd, and soil pH of 5.9. These findings provide valuable baseline data for the conservation and sustainable management of Araceae species in tropical riverine ecosystems.